Manajemen Risiko di Perguruan Tinggi Swasta - Mesiono Mesiono; Wahyuni Kesuma; Febrilian Lestario; Darmawati Harahap (Journal on Education, 2023)
As an important element in overall project planning, risk management identifies specific risks that could have an adverse effect on project performance and measures the impact each risk may have. As the project moves forward, the team continues to address risks with technical, administrative and budgetary strategies.. Get to know the four key stages in project risk management and the steps needed to manage risk. There are four distinct phases of project risk management: (1) risk identification, (2) probability and consequence analysis, (3) risk mitigation strategies, and (4) control and documentation. Risk identification focuses on determining a realistic set of risk factors facing the project. The five main causes of project risk are (1) financial risk, (2) technical risk, (3) commercial risk, (4) execution risk, and (5) contract or legal risk. Among the most common methods for risk identification are (1) brainstorming meetings, (2) expert opinion, (3) past history, and (4) multiple or team-based assessments. Risks can be mitigated through four main things: approach. First, we simply accept the risk. We may choose to do this in situations where we have no alternative or we deem the risk small enough to be acceptable. Second, we may seek to minimize risk, perhaps through partnerships or joint ventures to reduce our company's exposure to risk. Third, we may share risks with other organizations or project stakeholders. Finally, when necessary, we may seek to shift risk to other project stakeholders. Explanation of the Analysis and Project Risk Analysis and Management (PRAM) process. PRAM is a generic project risk management approach that offers a model for life cycle steps that a project team might adopt in developing a risk management methodology. The nine distinct steps in the PRAM model represent each process phase and their associated outcomes.